Macro and meso dynamic response of granular materials in ballastless track subgrade for high-speed railway - Junhua Xiao (Elsevier, 2021)
Considering the discrete and stochastic properties of granular materials, a two-dimensional numerical model was established to study the dynamic behavior of high-speed railway (HSR) ballastless track subgrade by using finite difference-discrete element (FDM-DEM) coupling method. Combined with on-site vibration test results in macroscopic scale, the mesoscopic vibration response of subgrade granular materials was analyzed under different speed levels. Some unusual phenomena were observed as follow: 1). In the surface layer (i.e., the top area of the subgrade, thickness = 0.4 m), particles showed a very wide response band in the frequency domain (up to 130 Hz), even beyond the maximum frequency of train loading (60 Hz). It was found that some particles in the surface layer produced not only forced vibration, but also local random vibration. However, the bottom layer particles (i.e., the area under the surface layer, thickness = 2.3 m) were only active within 40 Hz. 2) Force chains in the granular aggregate were disappeared and rebuilt synchronously in the dynamic loading process. A typical mode of force chain weakening was described in meso scale. 3) Particles at interface region between the surface and bottom layer exhibited severe local vibration amplification when the train speed level was higher than 300 km/h.